A GPU-based elastic shape registration approach in implicit spaces - Yousef, Ahmed Hassan; Abd El Munim, Hossam E. (Journal of real-time image processing, 2019)
In this paper, we present a GPU-based implementation of an elastic shape registration approach in implicit spaces. Shapes are represented using signed distance functions, while deformations are modeled by cubic B-splines. In a variational framework, an incremental free form deformation strategy is adopted to handle smooth deformations through an adaptive size control lattice grid. The grid control points are estimated by a closed-form solution which avoids the gradient descent iterations. However, even this solution is very far from real time. We show in detail that such an algorithm is computationally expensive with a time complexity of O ( N C P x N C P 2 X 2 Y 2 ) where N C P x and NCP are the grid lattice resolution parameters in the shape domain of size X × Y . Moreover, the problem becomes more time-consuming with the increase in the number of control points because this requires the execution of the incremental algorithm several times. The closed-form solution was implemented using eight different GPU techniques. Our experimental results demonstrate speedups of more than 150 × compared to the C implementation on a CPU.